Corylin protects LPS-induced sepsis and attenuates LPS-induced inflammatory response - Yung-Li Hung; Shih‐Hua Fang; Shu‐Chi Wang; Wei‐Chung Cheng; Po‐Len Liu; Chia-Cheng Su; Chi-Shuo Chen; Ming‐Yii Huang; Kuo-Feng Hua; Kun-Hung Shen; Yu-Ting Wang; Katsuhiko Suzuki; et al. (2017)
Abstract Corylin is a main compound isolated from Psoralea corylifolia L. (Fabaceae). A variety of pharmacological effects such as antioxidant, anti-proliferation, and anti-inflammatory properties of corylin have been reported. Nevertheless, the effect of corylin in microbial infection and sepsis remains unclear. In the present study, we investigated the anti-inflammatory effects of corylin. Our experimental results demonstrated that corylin inhibited the production of TNF-α, IL-6 and NO by both LPS-activated RAW 264.7 cells and LPS-activated murine peritoneal macrophages. Moreover, corylin suppressed the expression levels of iNOS and COX-2, reduced the production of PGE 2 and HMGB1, blocked the translocation of HMGB1 from the nucleus to cytosol, and decreased the phosphorylation of MAPKs in LPS-activated RAW 264.7 cells as well as suppressed the activity of NF-κB in LPS-activated J-Blue cells. In addition, the administration of corylin reduced the production of NO and TNF-α, decreased LPS-induced liver damage markers (AST and ALT) and kidney damage markers (BUN and CRE), attenuated infiltration of inflammatory cells and tissue damage of lung, liver and kidney, and enhanced the survival rate of LPS-challenged mice. Taken together, these results show the anti-inflammatory properties of corylin on LPS-induced inflammation and sepsis. Corylin could potentially be a novel anti-inflammatory and immunosuppressive drug candidate in the treatment of sepsis and septic shock.